Optimizing the Preparation of Your Own Estimated Price with a Reasonable Profit Procurement of Goods/Services for the Mayor of Binjai - Tiara Ermelia; Andri Soemitra (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2022)
Self Estimated Price, hereinafter referred to as HPS, is the estimated price of goods/services determined by the Commitment Making Officer, hereinafter referred to as PPK, which functions as an instrument to assess the fairness of the bid price and to determine the additional amount of performance guarantee value for bids deemed too low but cannot be used as a basis for canceling bids. The purpose of this study is to find out how to optimally prepare HPS so as not to create excessive profits so that there is no state loss. The method used in this research is qualitative and the type of this research is descriptive. The results show the lack of understanding carried out by PPK at the PBJ of the Regional secretariat of Binjai City in the perspective of the correct and inaccurate HPS compiler and does not control market prices and does not survey prices in the market. Profit + 15% overhead only for construction workers. The data used to prepare the HPS must be accountable and must be documented.